Improving teaching quality: Development of the PjBL microteaching model for prospective biology teachers - Ali Sadikin; Muhammad Rusdi; Muhammad Haris Effendi Hasibuan; Jodion Siburian (Biosfer)
Educational institutions prepare prospective biology teachers so they can carry out learning effectively and efficiently. However, there is a gap in meeting the needs for effective learning for prospective biology teachers. Based on a survey of 177 prospective teacher students, it was found that they preferred microteaching to be integrated with the project-based learning model. The aim of this research is to develop a PjBL-based microteaching model. The research method employed is Research and Development (R&D) using the ADDIE model. The research subjects were 36 fourth-semester students from the Biology Education Study Program who were enrolled in microteaching courses. The PjBL-based microteaching model has the syntax, (1) Instructional to the concept of microteaching, (2) plan, (3) teach, (4) feedback and reflection, (5) project collection, (6) project evaluation. Conclusion: This PjBL-based microteaching model is developed from microteaching and PjBL theories. The PjBL-based microteaching model for prospective biology teachers is deemed suitable for use, as indicated by validator assessments and small group and large group tests. Based on the results of the large group trials, it is evident that this model positively impacts the 4C skills of prospective biology teachers.